Results of an Inpatient Preventive Health Care Program to Improve Quality of Life, Psychosocial Health, and Work Ability in Austria - Bettina Thauerer; Johannes Püspök; Werner Kullich; David Felder; Bibiane Steinecker-Frohnwieser; Martin Skoumal (Frontiers Media S.A., 2023)
Objective: The Austrian Federal Pension Insurance (PVA) developed a preventive inpatient health program, "Gesundheitsvorsorge-Aktiv (GVA)," for patients with musculoskeletal disorders. Individualized modular interventions and therapeutical measures (movement optimization, movement motivation, and mental health) are designed to improve occupational participation by influencing lifestyle factors and health-related quality of life. The study aimed to evaluate the new prevention-oriented and more personalized inpatient health program GVA.Methods: Patients underwent a standard inpatient health program, with emphasis on exercise management, exercise motivation, or psychological aspects. Submodule-dependent outcomes were assessed in patients (n = 330) at the start, end of treatment, and 6 months thereafter. Quality of Life (EQ-5D-5L), psychosocial aspects of the Patient Health Questionnaire (PHQ-D), and Work Ability Index (WAI) were queried.Results: The results consistently showed positive short and long-term effects. The subjective assessments of current work ability improved while the impairment of work performance was reduced. Positive changes in the psychosocial sphere were observed, alongside improvements in the health-related quality of life. Patients in the exercise optimization module performed better in all respects.Conclusion: In summary, GVA represents a valuable preventive health measure that leads to a holistic increase in well-being and can also ensure the maintenance of the ability to work.